Adherence, persistence, and discontinuation among Hispanic and African American patients with multiple sclerosis treated with fingolimod or glatiramer acetate. (2nd January 2018) - Williams, Mitzi J.; Johnson, Kristen; Trenz, Helen M.; Korrer, Stephanie; Halpern, Rachel; Park, Yujin; Herrera, Vivian
Abstract: Objective: Few studies have examined compliance to disease-modifying therapies (DMTs) for multiple sclerosis (MS) in minority populations. This study compared adherence, discontinuation, and persistence for fingolimod (FTY) and glatiramer acetate (GA) initiators among Hispanic and African American patients with MS. Methods: This retrospective claims data study examined Hispanic and African American adults with MS who initiated FTY or GA between September 1, 2010 and June 30, 2014. Outcomes (adherence, discontinuation, and persistence) were analyzed descriptively and with multivariable models, comparing FTY and GA cohorts within racial/ethnic groups. Adherence was assessed using medication possession ratio (MPR) and proportion of days covered (PDC). Results: There were 171 patients in the Hispanic group (62 FTY, 109 GA) and 210 in the African American group (71 FTY, 139 GA). A larger proportion of GA initiators than FTY initiators were treatment-naïve; other baseline characteristics were similar between cohorts. Hispanic FTY initiators had greater mean MPR, PDC, and persistence and less discontinuation than GA initiators. African American FTY initiators had greater mean PDC than GA initiators; other outcomes favored FTY but were not statistically significant. Multivariable analysis results were consistent with the unadjusted results, but differences between treatment cohorts were not statistically significant. Conclusions: Hispanic and African American patients with MS who initiated FTY had higher adherence than those who initiated GA, similar to the general MS population. These findings suggest that adherence should be considered in DMT selection, and racial/ethnic variations in MS disease course may not be primarily attributable to differences in DMT compliance.